The vitamin D paradox: high prevalence of deficiency in sunny Athens (Greece) - Kyriakaki, Argyro; Fragkoulis, Evangelos (Annals of Research Hospitals, 2019)
There is a universal hype regarding vitamin D (vitD) and a belief that we are over-screening and over-treating population for vitD deficiency, especially in Athens, one of the sunniest cities in Europe. We studied 271 postmenopausal women (mean age: 67.3 years old) who had been referred for vitD level assessment to the microbiology lab of Peristeri’s Health Center during a period of three months (January–March 2017). The mean serum 25-hydroxy vitD [25-(OH)D] was 16.53±6.41 (ng/mL), which was unexpectedly low for a population living in a Mediterranean region, while a significant proportion of postmenopausal women in Athens appeared to suffer from hypovitaminosis D, varying from 39.5% to 92.2%, depending on the cut-off values we utilise to define the vitD deficiency. These data justify screening of perimenopausal women for vitD deficiency, as they indefinitely consist a high-risk group.